Comparative Study of Elisa and Iift in Detecting Chlamydia Pneumoniae Specific Igg Antibodies in Patients of Acute Coronary Syndrome (ACS) - Bhuva , S P; Bhuva , P J; Javdekar , T B; Jain , M R; Mulla , S A (National Journal of Community Medicine, 2012)
Background: Chlamydia pnaumoniae is reported to be associated with coronary heart disease (CHD). Efficacy of available serologic tests for detecting C.pneumoniae antibodies has been debated. The aim of present study was to compare Enzyme Linked Immunosorbant Assay (ELISA) and Indirect Immunofluorescent Test (IIFT) for detecting specific antichlamydial antibodies in patients of Acute Coronary Syndrome (ACS). Materials and Methods: Serum samples from 100 patients of ACS and 90 healthy controls were tested for the presence of Chlamydial IgG antibodies using ELISA and IIFT. To assess agreement between ELISA and IIFT, we used ‘nominal scale variables”. Agreement analysis was done using sensitivity, specificity, positive and negative predictive values (PPV and NPV) and diagnostic accuracy of the test. Results: The ELISA and IIFT detected C.pneumoniae IgG antibodies in 66% and 48% respectively in patients of ACS, and 29% and 20% respectively of healthy controls. In patients of ACS, sensitivity and specificity of ELISA as compared to IIFT were 70.8% and 38.4% respectively. The PPV of ELISA for C.pneumoniae was 51.5% and NPV was 58.8%. The diagnostic accuracy of ELISA for C.pneumoniae was 54.6%. The two tests correlated in 54% of samples with a moderate agreement of =0.51. Conclusions: The results of present study indicate that ELISA test was inferior to IIFT in detecting C.pneumoniae antibodies in patients of ACS.